Adding Fuel to the Fire: Alcohol’s Effect on the HIV Epidemic in Sub-Saharan Africa - Hahn, Judith A.; Woolf-King, Sarah E.; Muyindike, Winnie (Current HIV/AIDS Reports, 2011)
Alcohol consumption adds fuel to the HIV epidemic in sub-Saharan Africa (SSA). SSA has the highest prevalence of HIV infection and heavy episodic drinking in the world. Alcohol consumption is associated with behaviors such as unprotected sex and poor medication adherence, and biological factors such as increased susceptibility to infection, comorbid conditions, and infectiousness, which may synergistically increase HIV acquisition and onward transmission. Few interventions to decrease alcohol consumption and alcohol-related sexual risk behaviors have been developed or implemented in SSA, and few HIV or health policies or services in SSA address alcohol consumption. Structural interventions, such as regulating the availability, price, and advertising of alcohol, are challenging to implement due to the preponderance of homemade alcohol and beverage industry resistance. This article reviews the current knowledge on how alcohol impacts the HIV epidemic in SSA, summarizes current interventions and policies, and identifies areas for increased research and development.
Keywords: Alcohol consumption; HIV; Sub-Saharan Africa; Unprotected sex; HIV acquisition; HIV transmission; Alcohol biomarkers; Antiretrovirals; Antiretroviral adherence; HIV disease progression; Alcohol treatment; Alcohol policy